Acupuncture understood : rediscovering traditional five element healthcare - Lightbody, Stuart (World Scientific Publishing Co. Pte. Ltd., 2014)
Very little has been written on acupuncture and the Oriental medical view of health for the lay person in recent years. Even less has been written on the training requirements which vary enormously. This unique book clarifies this situation. It introduces the reader to the key concepts of healthy living, wellbeing, longevity, and their own inner kingdom. It draws upon the wisdom inherent in ancient Chinese philosophy whose universal principles were laid down in the Nei Jing, the oldest extant medical book in the world, written around 221 BCE. It brings alive and makes relevant this ancient understanding of the human being and the concept of health maintenance in the 21st century and is presented in a clear, easy to read and interesting format. It involves the individual in looking at their own health and lifestyle and offers advice as to how these might be optimised for life in the modern world. This book covers the historical background of oriental medicine, gives details of the 5 Element and Yin/Yang theories and brings to light its remarkable transition from one side of the world to the other. It explains how diagnosis, the consultation process, acupuncture and moxabustion work and offers extensive advice on preventive health.